DNA methylation in development and disease: an overview for prostate researchers - Joseph, Diya B (Am J Clin Exp Urol, 2018)
Epigenetic mechanisms including DNA methylation are critical regulators of organismal development and tissue homeostasis. DNA methylation is the transfer of methyl groups to cytosines, which adds an additional layer of complexity to the genome. DNA methylation marks are recognized by the cellular machinery to regulate transcription. Disruption of DNA methylation with aging or exposure to environmental toxins can change susceptibility to disease or trigger processes that lead to disease. In this review, we provide an overview of the DNA methylation machinery. More specifically, we describe DNA methylation in the context of prostate development, prostate cancer, and benign prostatic hyperplasia (BPH) as well as the impact of dietary and environmental factors on DNA methylation in the prostate.